Urban environment : Proceedings of the 11th Urban Environment Symposium (UES), held in Karlsruhe, Germany, 16-19 September 2012 - Morrison, Gregory; Norra, Stefan; Schleicher, Nina; Rauch, Sebastien (Springer Netherlands, 2013)
Over half of the global population now lives in cities. This ongoing urbanisation is making it increasingly important to adequately manage urban systems and preserve urban environments. This book is the outcome of the 11th Urban Environment Symposium (UES) held on 16-19 September 2012 in Karlsruhe, Germany. The UES aims at providing a forum on the sciences and practices needed to promote a sustainable future in urban environments. Papers by leading experts are presented in sections on Urban Management and Spatial Planning, Green Cities and Urban Ecosystems, Urban Planning and Development, Air Quality and Noise, Urban Climate Change and Adaptation, and Contamination of Urban Waters and its Effects.